2000
DOI: 10.1111/j.1540-8159.2000.tb00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Heart Rate Variations During Head‐up Tilt Table Testing as a Predictor of Outcome of the Test

Abstract: Head-up tilt table testing (HUTT) is a useful tool for the diagnosis of unknown origin of syncope. A setback is its duration. This study tries to establish a specific parameter that, according to the heart rate elevation in the test's initial phase, allows a reliable prediction of its outcome. In a prospective study, every patient being under unknown syncope workup was included. A two-phase 20-minute tilt table test was performed. The initial phase was passive, and the second required pharmacological stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The aim of our study was to identify the best early noninvasive hemodynamic predictor of nitroglycerin‐potentiated HUTT outcome in healthy patients with recurrent unexplained syncope. Clinical and experimental previous studies evaluated many parameters as possible predictors of positive HUTT response, such as clinical characteristics of the patients, HR, HR variability, BP oscillations, HR/BP ratio, and other hemodynamic changes during the test; however, none of them is routinely used in the clinical evaluation of patients with recurrent unexplained syncope.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of our study was to identify the best early noninvasive hemodynamic predictor of nitroglycerin‐potentiated HUTT outcome in healthy patients with recurrent unexplained syncope. Clinical and experimental previous studies evaluated many parameters as possible predictors of positive HUTT response, such as clinical characteristics of the patients, HR, HR variability, BP oscillations, HR/BP ratio, and other hemodynamic changes during the test; however, none of them is routinely used in the clinical evaluation of patients with recurrent unexplained syncope.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the patients without an exaggerated increase in HR in the first minutes of HUTT may be less likely to develop VVS during the test. Previous studies have analyzed whether the level of increase in HR monitored at the beginning of the HUTT predicts the final test result 5–7,13 . Many of these studies demonstrated an association between increase in mean HR during an early phase of tilting and final result of the test with different HUTT protocols 5,6,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have analyzed whether the level of increase in HR monitored at the beginning of the HUTT predicts the final test result 5–7,13 . Many of these studies demonstrated an association between increase in mean HR during an early phase of tilting and final result of the test with different HUTT protocols 5,6,13 . Furthermore, they have been presented cut‐off values for early increase in HR 5,6,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Since syncope is thought to result from excessive activation of the cardiac mechanoreceptors in response to the emptying of the heart (the Bezold-Jarisch reflex) [3], continuous recording of central haemodynamics could be helpful in improving the interpretation of HUT outcome. However, the haemodynamic variables usually collected during HUT remain limited to ECG and arterial pressure [4][5][6] because of technical and ethical limitations. Few studies have attempted to record cardiac haemodynamics during HUT in order to detect early abnormalities.…”
Section: Introductionmentioning
confidence: 99%